Against Social Abjection: Offred’s Empowering Narration of The Handmaid's Tale (1985) - Esmailzadeh, Saeedeh (Archīum Ateneo, 2024)
This scholarly investigation explores how Offred, the central character in Margaret Atwood’s The Handmaid’s Tale, endeavors to undermine the abjectifying apparatus of Gilead through the utilization of her narrative as a form of resistance. Drawing inspiration from Imogen Tyler’s concept of social abjection, the initial segment of this study will concentrate on the implementation of policies aimed at abjection within the society of Gilead. It will elucidate that the Gileadean regime employs tactics such as fostering disgust consensus, enforcing social hierarchies, propagating territorial stigmatization, and asserting control over language to execute the mechanisms of social abjection. This procedure serves to strip the Handmaids of their autonomy and agency, ultimately generating a populace mired in abjection. Nevertheless, the subsequent section of this study contends that Offred’s narrative effectively dismantles the aforementioned policies of abjection, thereby imbuing the protagonist with the necessary capacity for rebellion. Hence, this article elucidates that Offred’s narrative, notwithstanding its seemingly passive facade, emerges as the most appropriate mode of rebellion against the prevailing oppression she encounters in Gilead as this narrative effectively deconstructs the abjectifying societal structures imposed upon her.